PENGARUH GAYA PENGGUNAAN ANGGARAN, KOMPLEKSITAS TUGAS, KOMPLEKSITAS ORGANISASI DAN DUKUNGAN MANAJEMEN TERHADAP HUBUNGAN STRATEGI COST LEADERSHIP DAN PENINGKATAN KINERJA DI PT PERKEBUNAN NUSANTARA XI (PERSERO) - Suwandhi, Suwandhi; Armono, Drajat (Jurnal Bulletin, 2018)
The Influence of Budget Usage Style, Task Complexity, Organizational Complexity and Management Support on the Relationship of Cost Leadership Strategies and Performance Improvement at PT Perkebunan Nusantara XI (Persero). This study aims to examine whether the cost leadership program influences the performance of PT Perkebunan Nusantara XI (Persero). Contingency approach is widely used by researchers to find out whether the success of a company is influenced by the cost leadership strategy and always has the same effect on each condition. To explain this effect, four contingency factors, budget use, task complexity, organizational complexity and management support in cost control programs at PT Perkebunan Nusantara XI (Persero). Data collection method uses survey method, to test the hypothesis used Moderated Regression Analysis (MRA). The results of the study found that budget, task complexity, organizational complexity and management support were not moderating variables that could strengthen the relationship between cost leadership programs and performance improvements at PT Perkebunan Nusantara XI (Persero). The results of this study are expected to contribute to practitioners, to anticipate factors that can affect the company's performance. For academics to explain, how, when, and where budget use, task complexity, organizational complexity and management support are needed in order to improve the relationship between cost leadership programs and organizational success, by suggesting the nature of relationships that are influenced by different conditions